2021
DOI: 10.1038/s41598-021-91730-1
|View full text |Cite
|
Sign up to set email alerts
|

Trophic niches of native and nonnative fishes along a river-reservoir continuum

Abstract: Instream barriers can constrain dispersal of nonnative fishes, creating opportunities to test their impact on native communities above and below these barriers. Deposition of sediments in a river inflow to Lake Powell, USA resulted in creation of a large waterfall prohibiting upstream movement of fishes from the reservoir allowing us to evaluate the trophic niche of fishes above and below this barrier. We expected niche overlap among native and nonnative species would increase in local assemblages downstream o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…Another significant impact to the SRR riverscape includes the invasion of nonnative tamarisk and Russian olive (Elaeagnus angustifolia ), which has contributed to vertical accretion of fine sediments, enhanced streambank stabilization, channel narrowing and planform simplification (Manners, Schmidt, & Scott, 2014). The loss of a natural flow regime, as well as the invasion of nonnative vegetation, has caused the SRR to change from heterogenous, diverse and multi-threaded system to a highly aggraded, simplified and homogenous riverscape (Walker & Hudson, 2004;Pennock et al, 2021;). Specifically, between 1938 and, the system has narrowed 83% in the lower 90 km, and the floodplain has vertically accreted between 1.0 and 2.5 m (Fortney et al, 2011).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Another significant impact to the SRR riverscape includes the invasion of nonnative tamarisk and Russian olive (Elaeagnus angustifolia ), which has contributed to vertical accretion of fine sediments, enhanced streambank stabilization, channel narrowing and planform simplification (Manners, Schmidt, & Scott, 2014). The loss of a natural flow regime, as well as the invasion of nonnative vegetation, has caused the SRR to change from heterogenous, diverse and multi-threaded system to a highly aggraded, simplified and homogenous riverscape (Walker & Hudson, 2004;Pennock et al, 2021;). Specifically, between 1938 and, the system has narrowed 83% in the lower 90 km, and the floodplain has vertically accreted between 1.0 and 2.5 m (Fortney et al, 2011).…”
Section: Study Areamentioning
confidence: 99%
“…This degradation process is especially prevalent in the arid American Southwest, where four of the 14 fish species native to the Colorado River are considered threatened or endangered under the Endangered Species Act (ESA; Rinne & Minckley 1991;Laub et al, 2015). Remediating threats to the persistence of native biota in Southwest desert rivers will likely require coupled management of flow regimes and active in-channel restoration efforts in order to preserve and maintain crucial habitat (Propst, Gido, & Stefferud, 2008;Pennock, Ahrens, McKinstry, Budy, & Gido, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, trophic resource use studies can increase our understanding of changes to riverine food‐web structure and dynamics (McManamay et al, 2018; Vander Zanden et al, 2003). Because there is a scarcity of unaltered systems to use for comparisons, species or habitat compositional gradient studies are often conducted; however, but such investigations may not be able to detect a departure from conditions prior to severe alterations (Haubrock et al, 2020; Pennock et al, 2021; Rogosch & Olden, 2020; Turner et al, 2015). With the availability of museum specimens, the use of stable isotopes, and advances in statistical analyses, methods exist to detect departures from historical food‐web dynamics and may serve to identify proximate causes of continued species imperilment (Alp & Cucherousset, 2022; Turner et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, the concept of the isotopic niche was proposed, in which the axes of the multidimensional space are isotopic values that record bionomic and scenopoetic ecological information (Newsome et al ., 2007). Several authors have demonstrated that the isotopic niche is an important tool for exploring resource partitioning (Alves et al ., 2020), ontogenetic dietary shifts (Soares et al ., 2021) and niche overlap (Pennock et al ., 2021). This tool is especially useful for predator species, where the isotopic niche can provide a quantitative estimate of the energetic contribution and trophic level of prey species.…”
Section: Introductionmentioning
confidence: 99%